Transformasi Pelaksanaan Ilmu Sosial di Indonesia: Dari Citizenship Transmission Menuju Pembelajaran Kontekstual Abad 21 - Rohmah, Putri Adibatur; Hilman, Sukran Nizar; Ram, St Wijdanah; Muhammad, Ardiyana; Utami, Dinda Dwi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This study aims to examine the transformation of Social Sciences (IPS) learning in Indonesia, from the citizenship transmission approach to contextual learning in the 21st century. Using the literature study method, this study analyzed various sources such as books, journals, and articles related to the development of social studies education. The results of the study show that social studies in Indonesia has evolved from simply delivering civic values to more integrative and skill-based learning in the 21st century, such as critical thinking, creativity, collaboration, and communication. This change was influenced by the dynamics of the national curriculum, starting from the 1975 and 1984 Curriculum to the Merdeka Curriculum. The implementation of social studies learning now emphasizes interdisciplinary approaches, character development, and the use of innovative methods such as Project-Based Learning (PBL) and Inquiry-Based Learning. However, challenges are still found, including limited teacher competence, limited resources, and resistance to changes in learning methods. Therefore, it is necessary to increase teacher professionalism and strengthen innovation in learning to realize the goals of social studies education that is adaptive to the needs of the times. This study affirms the importance of social studies in shaping a generation that is critical, ethical, and ready to become agents of change in the midst of global complexity.